Realization of infrared display images using infrared laser projection method. (October 2021) - Choi, Yong Kyu; Pak, Jeong Hyeok; Seo, Keumyoung; Jeong, Sang-Mi; Lim, Taekyung; Ju, Sanghyun
Highlights: Infrared (IR) imaging technologies are used to analyze the shapes or heat distributions of objects via converting the thermal IR radiation emitted by the objects to IR images through IR-camera detection. Meanwhile, the arbitrary generation of IR images containing specific information can aid in the development of artificial intelligence (AI) devices with IR detection capabilities. Moreover, IR-enabled autonomous vehicles and robots of the future can generate, send, receive, and analyze IR image information. In this context, we propose a method to implement 2D and 3D IR displays using a laser-based IR-projection image-generation technique. IR images were generated using near infrared-to-long wave infrared (NIR-to-LWIR) conversion substrates and LWIR reflection substrates. By controlling the IR laser power and laser scan speed, we were able to generate full-color IR-emitting images (lines, letters, and shapes) on an IR camera screen. Furthermore, we were able to generate dynamic 2D and 3D IR images with the proposed system. With the 2D/3D IR projection imaging system proposed in this study, structures and moving objects in traffic environments can reproduced as IR images in a virtual 3D space. In addition, virtual IR images highly similar to the actual IR images of human faces and hands, vehicles, and airplanes can be created. It is also possible to encode information securely by combining encrypted codes with color codes. The IR projection display has addresses the problem of light pollution due to the indiscriminate use of displays and human-health-related problems due to radio-based information transmission because it allows entities to exchange specific information with each other without being perceived by the human eye. Abstract: In general, infrared (IR) images are generated based on the temperature distribution of the objects of interest by detecting the thermal IR radiation emitted from these objects with the help of sensors. However, the generation of information-specific IR images can enable "intelligent" entities such as autonomous vehicles and artificial intelligence robots with IR detection features to use IR images for exchanging information. In this context, here, we examine a method of realizing IR-image-based information using IR laser projection. With our approach, two- and three-dimensional IR images could be generated by converting near-IR rays to far-IR rays based on the heat generated by a laser. Importantly, the IR signals do not adversely affect humans or interfere with electronic devices. The proposed IR display can be used to exchange specific information among IR-detection-enabled entities without being detected by the human eye. Therefore, it is expected to overcome the problem of light pollution due to the indiscriminate use of displays and human-health-related problems arising from the exposure to electromagnetic wave-based information transmission.